Examining constructs of beauty through literature - Kur, Samantha (My University, 2009)
ABSTRACT The aim of this research was to explore how literature can be utilised to help adolescents better understand themselves and the world around them. I focused the research on the issue of beauty. The research was conducted with a group of three female Grade 10 learners in a school in a North East suburb of Johannesburg. The research centred on a study of Toni Morrison’s novel The Bluest Eye and a workbook created to employ the novel as a catalyst for discussions and activities around aspects of beauty. This novel was selected because of the presence of the theme of unattainable beauty. Throughout the research period the learners explored their own notions of beauty as they read the novel and used the workbook. The theoretical framework of this research draws on reader response theory as outlined by Louise Rosenblatt in order to explore how the reading of literature has the potential to help learners understand the world around them. The research also draws on the theory of feminist poststructuralism as theorised by Chris Weedon in order to examine how the learners have come to understand beauty and how they react to the text. The theory of critical literacy is used to shed light on the possibility of the learners rejecting any new constructs of beauty. The theoretical framework also provides a survey of various theories of beauty that illustrate how adolescents are influenced by a socially constructed Gaze and by the media. The framework also explores alternatives to the dominant construct of beauty. Lastly, the theoretical framework discusses how race has influenced constructs of beauty. The content of the data revealed that the learners were profoundly impacted by peer gazing. Comments and looks from their peers caused the participants to judge themselves according to a standard of beauty created by their peers, in turn affecting the learners’ self esteem. The analysis of the data showed that the media was another determining factor in the participants’ construct of beauty. The participants, through a variety of media, absorbed the notion of the ‘beautiful’ female body as the ideal to which they should aspire. Furthermore the participants expressed a feeling of being different under the racist Gaze which caused them to question the validity of their skin colour, their noses and their hair in relation to white normative constructs they had internalised. By the end of the research programme the participants seemed unable completely to move away from the influence of the dominant construct of beauty. They still judged themselves according to the standards projected by the media and their peers. However, the analysis of the data also shows how the participants, by the end of the research, were able to demonstrate some attitudinal change towards their bodies and to articulate an alternative concept of beauty that included positive personality traits and objects of non-visual beauty. The participants also exhibited a heightened awareness of a dominant construct of beauty and actively resisted the dominant discourse of beauty projected by the media and their peers. This research proves that the literary experience, as described by Rosenblatt, plays an important part in the teaching of literature, providing readers with the opportunity to live through the experiences of the characters in the novel. This research shows that, to a limited extent, literature can affect the learners’ worldview.